Impact of silver diamine fluoride on composite resin bond strength: An In vitro study with various adhesive systems - Farzaneh Shirani; Shirin Ravanbod; Mohammad Soroush Sehat (Heliyon)
Aim: This in vitro study investigates the effects of Silver Diamine Fluoride (SDF) application on the shear bond strength (SBS) of resin composite to sound and demineralized human teeth using different adhesive systems. Methods: Eighty sound human third molars were sectioned, mounted in acrylic blocks, and prepared to expose a 2 mm thick dentin layer. The teeth were randomly divided into eight groups, each representing a combination of sound or demineralized dentin, SDF application, and adhesive system used. Demineralization was achieved using a pH cycling process. SDF was applied to the designated groups, followed by the use of either an etch-and-rinse or self-etch adhesive system. Resin composite was then applied, and the SBS was measured using a universal testing machine. Data were analyzed using three-way ANOVA and post-hoc tests to identify significant differences. Results: The application of SDF generally led to a significant decrease in bond strength (p < 0.05). In sound dentin, the SBS was higher compared to demineralized dentin (p < 0.05). OptiBond FL showed higher bond strength than Clearfil SE Bond across all groups, although the difference was not statistically significant (p > 0.05). The bond strength in the demineralized group using Clearfil SE Bond showed no significant difference between SDF application and non-application (p > 0.05). Conclusion: SDF application can significantly reduce the bond strength of resin composite to dentin, with the effect being dependent on the type of adhesive system and the state of the dentin. Further in vivo studies are needed to validate these findings.